The Urotensin II System and Carotid Atherosclerosis: A Role in Vascular Calcification - Albanese, Isabella; Daskalopoulou, Stella S.; Yu, Bin; You, Zhipeng; Genest, Jacques; Alsheikh-Ali, Alawi; Schwertani, Adel G. (Frontiers in Pharmacology, 2016)
Background and aims: The aims of the present study were to determine the expression of urotensin II (UII), urotensin-II related peptide (URP) and their receptor (UT) in stable and unstable carotid atherosclerosis, and determine the effects of UII on human aortic smooth muscle cell (SMCs) calcification. Methods and Results: We examined UII, URP and UT protein expression in 88 carotid endarterectomy specimens using immunohistochemistry. Expression of UII, URP and UT was more evident in unstable compared to stable plaques (P<0.05). Multivariate Spearman correlation analyses revealed significant positive correlations between UII, URP and UT overall staining and presence of calcification, severity of stenosis and inflammation (P<0.05). Subjects undergoing carotid endarterectomy had significantly higher plasma UII levels, as assessed by ELISA, when compared with normolipidemic healthy control subjects (P<0.05). Incubation of human aortic SMCs cultured in phosphate media with varying concentrations of UII resulted in a significant increase in calcium deposition and alkaline phosphatase activity. UII also significantly increased β-catenin translocation and expression of ALPL, BMP2, ON and SOX9 (P<0.05). Incubation of cells with phosphate medium alone increased the expression of the pre-UT and mature UT (P<0.01), and addition of UII had a synergistic effect on pre-UT protein expression (P<0.001) compared to phosphate medium alone. Conclusions: Upregulation of UII, URP and UT in unstable carotid endarterectomy plaques and plasma, and the stimulatory effect of UII on vascular smooth muscle cell calcification suggest that the UII system may play a role in the pathogenesis of vascular calcification and stability of atherosclerosis.